Perkembangbiakan Perkici Pelangi (Trichoglossus haematodus) di Laboratorium Penangkaran - W. Widodo (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
The research was conducted to understand the breeding aspects of the Rainbow Lorikeet (Trichoglossus haematodus), which were caged in flocks and as a pair, in two aviaries of the Animal House Laboratory of Zoological Division, the Research Center of Biology, Indonesian Institute of Sciences (LIPI), Cibinong. From January 2002 until January 2005, 11 birds of the Rainbow Lorikeets were used in this research,. The birds were divided into two groups, the first group (9 individuals)  were caged in the first aviary  and the second one (2 individuals) were caged in the second aviary. The  size of each aviary room (LxWxH) was 3.32 m x 1.82 m x 2.85 m. The aviary rooms were equiped with the roosting, nest boxes, feeding and drinking water places. Foods and water were given in cafetaria everyday, starting from about 08.00 a.m. The foods consisted of bird food/”pur” (150 grams), white bread (15 grams), cooked quail eggs (60-70 grams), the lampung bananas (300 grams), slices of corn (100 grams), bean sprouts (50 grams), and palm sugar (50 grams). All of the igredients were mixed with 450-500 ml water and were then pulverized. The birds were also given some vegetables. The results were as follows: the Rainbow Lorikeets caged in flocks have produced two chicks and those in a pair only produced one chick. The clutchs consisted of  1-2 eggs. Eggs were white, smooth and their shape ovale. Average weight of the eggs was 7-8 grams. Weight of day old chicks was about 8 grams, those chicks were still blind and with out featheres (“altricial”). Incubation periods was 25-26 days, and incubated either by the female or the male. Fledging period was 71 days or more. The growing of the featheres and young birds of the Rainbow Lorikeets will be also discussed in this paper.